Deconstruction of Visual Aesthetics and Ideological Myths of Digital Preaching on the Instagram Account @hanan_attaki - Iin Indrawati Budi Utami; Dewi Anggrayni (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2026)
This study examines the evolution of religious messaging in the digital realm, driven by the need to understand the impact of visualization on young audiences' perceptions of faith amidst increasingly crowded social networks. The research aims to dissect the formation of meaning in online da'wah activities by examining the complex blend of visual elements and storylines on the Instagram account @hanan_attaki from 2021 to 2025. The primary focus is on examining how religious intermediaries transform conventional teachings into emotionally charged personal experiences, presented specifically for Gen Z. Using a descriptive qualitative approach through virtual ethnography and Roland Barthes's semiotic analysis, this study meticulously breaks down digital codes down to the levels of denotation, connotation, and myth. This methodology allows for an in-depth exploration of how digital content creators manipulate symbols to align with contemporary sensibilities. The study reveals that the use of cinematic backdrops, soothing color gradations, and intimate appearances successfully constructs a significant new ideological myth: "Islam as Aesthetic Healing ." This semiotic transformation integrates religious rituals into the framework of modern life, effectively bridging the gap between noble values ​​and the fast-paced nature of digital culture. The study's conclusion emphasizes that while visual appeal is a key gateway for maintaining spiritual messages' relevance in the digital age, there is a real threat of watering down the essence of rich religious teachings into mere lifestyle symbols. This study offers a needed critical perspective on how faith is conveyed, emphasizing that efforts to achieve digital interaction and visual appeal should not override the depth of theological substance. Ultimately, this research suggests that transforming religious symbols into merchandise on Instagram creates a paradoxical situation: faith becomes more accessible but risks being diluted when consumed.